Qualitative research in nursing : advancing the humanistic imperative - Streubert, Helen J.; Carpenter, Dona Rinaldi (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Qualitative Research in Nursing is a user-friendly text that systematically provides a sound foundation for understanding a wide range of qualitative research methodologies, including triangulation. It approaches nursing education, administration, and practice and gives step-by-step details to instruct students on how to implement each approach. Features include emphasis on ethical considerations and methodological triangulation, instrument development and software usage; critiquing guidelines and questions to ask when evaluating aspects of published research; and tables of published research that offer resources for further reading"--Provided by publisher.
Philosophy and Theory: Foundations of Qualitative Research / Helen J. Streubert Speziale -- The Conduct of Qualitative Research: Common Essential Elements / Helen J. Streubert Speziale -- Designing Data Generation and Management Strategies / Helen J. Streubert Speziale -- Ethical Considerations in Qualitative Research / Dona Rinaldi Carpenter -- Phenomenology as Method / Dona Rinaldi Carpenter -- Phenomenology in Practice, Education, and Administration / Dona Rinaldi Carpenter -- Grounded Theory as Method / Dona Rinaldi Carpenter -- Grounded Theory in Practice, Education, and Administration / Dona Rinaldi Carpenter -- Ethnography as Method / Helen J. Streubert Speziale -- Ethnography in Practice, Education, and Administration / Helen J. Streubert Speziale -- Historical Research Method / Sandra B. Lewenson -- Historical Research in Practice, Education, and Administration / Sandra B. Lewenson -- Action Research Method / Helen J. Streubert Speziale -- Action Research in Practice, Education and Administration Action / Helen J. Streubert Speziale -- Triangulation as a Qualitative Research Strategy / Dona Rinaldi Carpenter -- Writing a Qualitative Research Proposal / Dona Rinaldi Carpenter -- A Practical Guide for Sharing Qualitative Research Results / Helen J. Streubert Speziale.
Includes bibliographical references and index.
Keywords: NURSING RESEARCH -- METHODS